An Analysis of How Mother Tongue(L1) Affects Teaching and Learning English Language(L2) in Schools in Mpondwe-Lhubiriha Town Council Kasese District. - Kule, Josephat (Kabale University, 2025)
This study focused on the role of the mother tongue in teaching and learning English, comparing grammatical structures and exploring measures to enhance the quality of English spoken, taught, and learned in schools in Mpondwe-Lhubiriha Town Council. The researcher investigated how the mother tongue influences learners' performance in written English, the effects of the mother tongue on their performance, and strategies to reduce its impact on English language proficiency in Mpondwe-Lhubiriha Town Council schools. Stratified and random sampling techniques were employed to ensure each individual had an equal chance of being included in the sample. Data was collected using a questionnaire, with fifty participants involved. The results revealed that the mother tongue has a significant influence on learners' performance in written English at the primary level, with a clear relationship between the two variables, as evidenced by the subjects' responses in their English language evaluation tests.